2014
DOI: 10.1101/005066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Independent Theta Phase Coding Accounts for CA1 Population Sequences and Enables Flexible Remapping

Abstract: SUMMARYPopulations of hippocampal place cells encode an animal's past, current and future location through sequences of action potentials generated within each cycle of the network theta rhythm. These sequential representations have been suggested to result from temporally coordinated synaptic interactions within and between cell assemblies. In contrast, we show that a model based on rate and phase coding in independent neurons is sufficient to explain the organization of CA1 population activity during theta s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 48 publications
(104 reference statements)
0
30
0
Order By: Relevance
“…To study the impact of synaptic clustering under in vivo-like conditions in the biophysical models we carefully matched the inputs of the models to the synaptic inputs experienced by these neurons in vivo. Inputs, corresponding to synaptic release events, were generated by a Generalised Linear Model (GLM) tuned to a number of different external and internal features (Pillow, 2007;Chadwick et al, 2015). Specifically, the presynaptic input count at time t for synapse i were generated from a Poisson process with rate λ i t :…”
Section: Inputsmentioning
confidence: 99%
“…To study the impact of synaptic clustering under in vivo-like conditions in the biophysical models we carefully matched the inputs of the models to the synaptic inputs experienced by these neurons in vivo. Inputs, corresponding to synaptic release events, were generated by a Generalised Linear Model (GLM) tuned to a number of different external and internal features (Pillow, 2007;Chadwick et al, 2015). Specifically, the presynaptic input count at time t for synapse i were generated from a Poisson process with rate λ i t :…”
Section: Inputsmentioning
confidence: 99%
“…Statistical models have shown that the precise trial-to-trial timing can be predicted by the spiking activity of other neurons, as would be expected if sequencing was brought about through a chaining of co-active ensembles oscillating faster than the baseline LFP (Harris et al 2002;Dragoi and Buzsáki 2006;Geisler et al 2007). However, principal cells respond to many environment stimuli and therefore a misspecification of the model may mistake common external modulation for a causal network interaction (Chadwick et al 2015). Therefore further experimentation is needed to resolve whether theta sequences truly reflect network level synchronization.…”
Section: The Hippocampus Organizes the Spatial Code Into Temporal Seqmentioning
confidence: 99%
“…The analysis of tree branching provides an estimate of the statistical dependencies between spike trains, independent of the underlying type of interaction and without assuming a particular transfer function for the target neuron [Harris et al, 2003]. The nature of neuronal coordination as observed from spike trains is still debated, for example in the hippocampus [Chadwick et al, 2015], and unbiased, model-free methods may be highly informative on the nature of the actual statistical dependencies between neurons.…”
Section: Discussionmentioning
confidence: 99%